2020
DOI: 10.1021/jacs.9b12918
|View full text |Cite
|
Sign up to set email alerts
|

Cerium(IV) Carboxylate Photocatalyst for Catalytic Radical Formation from Carboxylic Acids: Decarboxylative Oxygenation of Aliphatic Carboxylic Acids and Lactonization of Aromatic Carboxylic Acids

Abstract: We found that in situ generated cerium(IV) carboxylate generated by mixing the precursor Ce(O t Bu) 4 with the corresponding carboxylic acids served as efficient photocatalysts for the direct formation of carboxyl radicals from carboxylic acids under blue light-emitting diodes (blue LEDs) irradiation and air, resulting in catalytic decarboxylative oxygenation of aliphatic carboxylic acids to give C−O bond-forming products such as aldehydes and ketones. Control experiments revealed that hexanuclear Ce(IV) carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 56 publications
4
104
0
2
Order By: Relevance
“…Conducting the reaction under air (entry 5) or with the organic catalysts 4b-4e resulted in decreased yields (entries 6-9). Thee lectrophotocatalyticd ecarboxylative alkylation reaction was found to be compatible with primary (7)(8)(9)(10)(11)(12), secondary (13)(14)(15)(16)(17), tertiary (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and a-alkoxy (29-32) aliphatic carboxylic acids,d espite the fact that alkyl radicals derived from the latter two were prone to further oxidation (Scheme 2). Furthermore,avariety of N-heterocycles,including several drug molecules,w ere well tolerated.…”
Section: Entrymentioning
confidence: 99%
“…Conducting the reaction under air (entry 5) or with the organic catalysts 4b-4e resulted in decreased yields (entries 6-9). Thee lectrophotocatalyticd ecarboxylative alkylation reaction was found to be compatible with primary (7)(8)(9)(10)(11)(12), secondary (13)(14)(15)(16)(17), tertiary (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and a-alkoxy (29-32) aliphatic carboxylic acids,d espite the fact that alkyl radicals derived from the latter two were prone to further oxidation (Scheme 2). Furthermore,avariety of N-heterocycles,including several drug molecules,w ere well tolerated.…”
Section: Entrymentioning
confidence: 99%
“…Based on the above studies and previous literature reports, [15,18] ap ossible mechanism for the electrophotocatalytic decarboxylative CÀHalkylation and carbamoylation was proposed using lepidine as amodel substrate.T he alkylation reaction commences with the anodic oxidation of Ce III to Ce IV (Scheme 5d). Thelatter coordinates with the carboxylic acid…”
Section: Angewandte Chemiementioning
confidence: 87%
“…Forschungsartikel under air (entry 5) or with the organic catalysts 4b-4e resulted in decreased yields (entries 6-9). Thee lectrophotocatalyticd ecarboxylative alkylation reaction was found to be compatible with primary (7)(8)(9)(10)(11)(12), secondary (13)(14)(15)(16)(17), tertiary (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and a-alkoxy (29-32) aliphatic carboxylic acids,d espite the fact that alkyl radicals derived from the latter two were prone to further oxidation (Scheme 2). Furthermore,avariety of N-heterocycles,including several drug molecules,w ere well tolerated.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Tsurugi, Satoh, Mashima, and co-workers revealed that formation of an oxygen-bridged hexanuclear Ce cluster has important roles in highly activated photocatalysts. 125 In situ generation of Ce IV carboxylate upon mixing of the precursor Ce(OtBu)4 and the corresponding carboxylic acids worked as efficient photocatalysts to give carboxyl radicals from carboxylic acids with blue light irradiation. Decarboxylative oxygenation of aliphatic carboxylic acids to result in C-O bond products such as aldehydes and ketones was catalytically proceeded.…”
Section: Molecular Machine and Molecular Functionmentioning
confidence: 99%